Inkonsistensi Penegakan Hukum terhadap Tindak Pidana Perkawinan Halangan Menurut Pasal 279 KUHP Di Provinsi Aceh - Ahmad Buchori; Mohd. Din; Sulaiman Sulaiman (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Obstacle marriage is a criminal act prohibited in Article 279 of the Criminal Code, categorized as a crime of origin of marriage. Law enforcement against perpetrators of criminal acts mentioned in Article 279 of the Criminal Code is still experiencing inconsistencies, considering that crimes against the head of marriage have different interpretations from law enforcers. The purpose of this study is to look at the law enforcement process against criminal acts as an impediment to marriage in Aceh and to find out the reasons for the inconsistency of law enforcement against marriage crimes. The method in this study uses an empirical approach, which this approach combines legal and empirical (field) studies. Data collection techniques in this study using interviews. The results of the study indicate that law enforcement carried out by law enforcement officers such as the police, prosecutors and courts still have different understandings of the elements of criminal acts in Article 279 of the Criminal Code. This difference can be seen from the understanding of Article 279 of the Criminal Code regarding barriers to marriage. The lack of consistency in the law enforcement process for violations of Article 279 is because the law in Indonesia does not adhere to a legally binding system of jurisprudence in imposing criminal charges so each judge can interpret the article differently. In this regard, policymakers should provide clear conditions regarding violations of the origin of marriage in Article 279 of the Criminal Code, so there is no interpretation among law enforcement officers.